TUMPANG TINDIH SERTIPIKAT DI KELURAHAN PEGADUNGAN, KOTA ADMINISTRASI JAKARTA BARAT: Overlapping Certificates in Pegadungan Village, West Jakarta Administrative City - Desty Rachmawaty; Dinda Keumala (Universitas Trisakti, 2024)
Overlapping certificates are the issuance of two or more certificates describing the same parcel of land. The formulation of the problem in this research is whether the issuance of Title Certificate Number 9567/Pegadungan in the name of Yahya H. Ahmad above Building Rights Title Certificate Number 15596/Pegadungan in the name of PT Cakradigdaya Lokaraya is valid according to the provisions of National Land Law. Normative juridical research type with analytical descriptive research nature and the type of data used is secondary data obtained from the literature study. Data analysis using qualitative method and deductive inference. Conclusion, based on the Certificate of Pegadungan Village Head, the girik used by Yahya H. Ahmad in the issuance of Title Certificate Number 9567/Pegadungan is not registered in Pegadungan Village, so the issuance of Title Certificate Number 9567/Pegadungan is not in accordance with the provisions of National Land Law, namely the Explanation of Article 24 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration.